INFLUENCE OF COMMON MENTAL DISORDERS ON PREGNANT WOMEN: A NARRATIVE REVIEW - Eduardo da Silva Pereira , Marcos; Soares da Costa, Douglas; Clara Coutinho de Oliveira, Ana; de Lima Amorim , Tainá; Carneiro Medeiros , Eliana; Karla de Mesquita Silva, Diana; Eduarda Ferraz Vilarinho Oliveira , Maria; Vieira de Sousa Vilarinho, Adriana; Leite Nunes Silva Alves, Alanna; Vieira de Sousa Miranda, Cristina (Health and Society, 2023)
This narrative review addresses the prevalence and implications of Common Mental Disorders (CMDs) in pregnant women, highlighting the need for early detection and intervention. Systematic research across databases identified a high rate of CMDs in pregnant women, with variances across studies, some showing prevalences as high as 57.1%. Symptoms of CMDs are often confused with typical hormonal and emotional changes during pregnancy, making diagnosis and treatment challenging. This review underscores the urgency of clinical approaches and public policies focused on maternal mental health, targeting both the well-being of the mother and the fetus